A arquitetônica de charges com contornos intolerantes : discursos sociais em tensão - Gonçalves, Tamiris Machado (2019)
In contemporaneity, much has been discussed concerning hate speech. Charlie Hebdo’s case, occurred in 2015, at France, for instance, brought up several issues regarding the theme: cartoons versus intolerant speech. In Brazil, the political scenario, in its turn, exhibits, by means of social discourses materialized on the most diverse genres, tensions that polarize opinions and produce intolerance and hatred. Regarding this discussion, it is also considered the problem that circumscribes such concepts as “freedom of speech” – the rightful freedom of exposure, lacking on fear of censure or possible retaliations – and “hate speech” – referring to the propagation of ideas liable to criminal punishment measures. The research here presented, beholding this issue, studies in cartoon the functioning of intolerant discourses, based on guiding questions which inquire what intolerance is; how does it express itself on discourse; how can it be expressed in cartoons. Assumed this viewpoint, it is aimed to understand the discursive constitution of cartoon displaying intolerant contours, namely, its architectural. The specific goals are a) to understand the tensioning between freedom of speech and intolerant manifestation; b) to comprehend which resources are mobilized in order to edify intolerant senses; c) to identify which dialogical wires are necessary for a cartoon to be understood as a display of intolerant contours; d) to analyze constitutive elements regarding social discourses to perceive what they may reverberate in terms of sense; and e) to define the concepts of hatred and intolerance. For this, as to talk about intolerance presupposes a social view into discourses and their effects of sense, theoretically, it was built an interface between the areas of Discourse, Hermeneutical Law and Philosophy to carry out the analyses. In these terms, to understand how is edified the projection of intolerant senses in cartoons, on discourse, the theoretical and methodological foundations on Bakhtin Circle, specially on such concepts as: valuation, discursive genres and architectural. For Hermeneutic Law, there is foundation on the interpretation of Brazilian Constitution, in order to deliberate over the notions of freedom of speech and hate crime, as to also understand the difference between hate crime and intolerant manifestation. Regarding Philosophy, the notions of hatred and intolerance are sought. With the discussion, it is expected to be presented a methodological alternative to the comprehension of cartoons, mainly with regards to the criticism conveyed by such a genre. To do so, the constitutive elements from cartoons are approached relatively to their social face, in order to perceive its cultural implications, as well as the discursive projections. The more one thinks about the relations there are between everything that constitutes the cartoon, tensioned by social circumstances which motivate them, the more one shall know about its functioning. As for the results, the analyses indicate cartoon is critical discursive genre, displayed as a subject appreciation about social themes circumscribed by them. So, a cartoon may reverberate various sense effects: humor, irony, affront. It has been observed that the analyzed cartoons turn themselves into intolerant social discourses. In such a production, its projection of saying assumes, at a first glance, a complaint against the social discourse to which it is related in an enunciative chain. However, a deeper analysis exhibits that the cartoon itself projects senses of intolerance as a whole discourse which reverberates judgmental values.